Estados, transitividad y clíticos - Devís Márquez, Pedro Pablo (El Colegio de México, 2019)
The existence in Spanish of transitive constructions with stative predicates and a non-reflexive paradigmatic clitic that agrees with the subject in number and person (El alumno se supo la lección) raises important problems for accounts where this clitic is an aspectual operator that either only occurs with telic and durative predicates or is not related to telicity, or is a marker that conveys some involvement on the part of the sentence subject or a closer relationship between subject and DO. Beside reviewing these problems, the article sets out to explain: 1) the (in)compatibility of some transitive stative predicates with this clitic, 2) the compatibility of certain transitive stative predicates with the clitic when the relevant DOs are bare plurals, and3) the compatibility of certain transitive stative predicates with the clitic when their DOs are not bare plurals and lack explicit determiners.